2022
DOI: 10.3390/su14010498
|View full text |Cite
|
Sign up to set email alerts
|

Drying Shrinkage, Sulphuric Acid and Sulphate Resistance of High-Volume Palm Oil Fuel Ash-Included Alkali-Activated Mortars

Abstract: Nowadays, an alkali-activated binder has become an emergent sustainable construction material as an alternative to traditional cement and geopolymer binders. However, high drying shrinkage and low durability performance in aggressive environments such as sulphuric acid and sulphate are the main problems of alkali-activated paste, mortar and concrete. Based on these factors, alkali-activated mortar (AAM) binders incorporating high-volume palm oil fuel ash (POFA), ground blast furnace slag (GBFS) and fly ash (FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…Ranjbar et al [ 125 ] studied the compressive strength and microstructural analysis of FA-POFA-based geopolymer mortar and found that the increase in POFA/FA ratio increased the SiO 2 /Al 2 O 3 ratio leading to a decrease in early age strength and later gradual strength gains attributed to the reaction of aluminate species in early stages/scarcity of Al at later stages, and dominance in the reaction of silicate species at later stages. Similar results were obtained by [ 126 ], who attributed the loss in strength to a decrease in the dense gel formation and changes in crystallinity as the POFA replacement levels increased from 50–70% by weight of GGBFS. Figure 13 shows the FTIR of alkali-activated materials prepared with different levels of POFA.…”
Section: Resultssupporting
confidence: 89%
“…Ranjbar et al [ 125 ] studied the compressive strength and microstructural analysis of FA-POFA-based geopolymer mortar and found that the increase in POFA/FA ratio increased the SiO 2 /Al 2 O 3 ratio leading to a decrease in early age strength and later gradual strength gains attributed to the reaction of aluminate species in early stages/scarcity of Al at later stages, and dominance in the reaction of silicate species at later stages. Similar results were obtained by [ 126 ], who attributed the loss in strength to a decrease in the dense gel formation and changes in crystallinity as the POFA replacement levels increased from 50–70% by weight of GGBFS. Figure 13 shows the FTIR of alkali-activated materials prepared with different levels of POFA.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, the selection of suitable proportions of the mineral admixtures is very important to optimize the performance of GPMs. It was shown that the inclusion of FA can enable the formation of some 3D networked N-A-S-H gels, restraining the shrinkage of C-A-S-H gels [ 58 ]. According to Humad et al [ 59 ], the addition of FA in the AAS mixture can significantly mitigate its autogenous shrinkage without exhibiting considerable effects on its drying shrinkage.…”
Section: Resultsmentioning
confidence: 99%
“…So far, only a few studies have suggested that the incorporation of FA in the geopolymer matrix can enhance the shrinkage of GPMs [ 55 ]. The effects of FA addition on the drying shrinkage were attributed mainly to the increased porosity and reduced tortuosity of GPMs [ 58 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, environmental activists and concerned officials in different nations have been inspiring the cement sector to decrease its release of carbon dioxide [ 6 , 7 , 8 ]. There are two methods of reducing the utilization of cement, the 1st is the usage of blended cement, and the 2nd is the usage of alkali-activated granulated blast furnace slag (GBFS) [ 9 ], rice husk ash (RHA) [ 10 ], fly ash (FA) [ 11 ], palm ash [ 4 , 12 , 13 ], or any other material with rich aluminosilicates [ 14 ]. Using alkali-activated materials [ 11 ] uses less energy and decreases carbon dioxide’s outflow.…”
Section: Introductionmentioning
confidence: 99%